COLLOCATIONS ON BBC ONLINE NEWSPAPER - Anwar, Linzia; Jasin, Hamida A.; Bahara, Susana R (Jurnal Bilingual, 2024)
The aim of this research is to identify the types of lexical collocations and the most dominant types of lexical collocations in the BBC online newspaper. The online newspaper serves as the object of this research, and the subjects of the research are news articles from the BBC online newspaper. The method used in this research is a qualitative method with a content analysis approach. Content analysis is used to obtain and analyze data. Data is analyzed using the theory of Benson, M., Benson, E., Ilson (1986). There are seven types of lexical collocations according to Benson and Ilson, namely: verb (usually transitive) and noun/pronoun (or prepositional phrase), verb (meaning eradication and or nullification) and a noun, adjective and noun, noun and verb, noun and noun, adverbs and adjectives, and verbs and adverbs. The findings show that there are 24 lexical collocations. Of the seven types of lexical collocations, only four types of lexical collocations are found in the BBC online newspaper, namely Verb (usually transitive) + noun/pronoun (or prepositional phrase) amounting to 1 lexical collocation data or 4.16%. Verb (meaning eradication and/or nullification) + noun, 1 collocation of lexical data or 4.16%. Adjectives + nouns account for 16 lexical collocation data or 66.66%. And finally noun + noun with 6 lexical data collocations or 25%. Meanwhile, the types of lexical collocations of nouns and verbs, adverbs and adjectives and verbs and adverbs, were not found in the BBC online newspaper. The final conclusion is that the most dominant types used in the BBC online newspaper are adjectives and nouns, namely 16 data or in the form of a percentage of 66.66%.